Juridical Study of the Settlement of Land Dispute Case of Laba Pura Bukit Jati in Bangli Regency - Ardani, Ni Ketut; Sastrini, Luh Ketut Ayu Manik; Adnyani, Ni Putu Rahayu Mely (PT FORMOSA CENDEKIA GLOBAL, 2024)
Based on this theory, the Laba Pura area is the Kanista Mandala Pura, or the temple grounds outside the temple itself. The focus of this research is to conduct a thorough investigation of the land dispute in Bukit Jati Temple, Bangli Regency. Therefore, it is expected that Pengempon Pura is able to manage Pura Profits creatively in order to help maintain a harmonious balance in temple operations. Normative legal research is the research methodology used in this thesis. People easily divert Pura Profit land because they consider it as ordinary land, just like other agricultural properties. Efforts to preserve customary land must be watched by the government and temple owners, therefore Laba Pura land or also known as Pelaba Pura land needs legal protection. Legal certainty usually views the trustworthiness of the transfer of land rights in Laba Pura as equivalent to the transfer of land ownership rights.